Wuhan to World: The COVID-19 Pandemic - Kumar, Ashok; Singh, Rita; Kaur, Jaskaran; Pandey, Sweta; Sharma, Vinita; Thakur, Lovnish; Sati, Sangeeta; Mani, Shailendra; Asthana, Shailendra; Sharma, Tarun Kumar; Chaudhuri, Susmita; Bhattacharyya, Sankar; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
COVID-19 is a Severe Acute Respiratory Syndrome (SARS), caused by SARS-CoV-2, a novel virus which belongs to the family Coronaviridae. It was first reported in December 2019 in the Wuhan city of China and soon after, the virus and hence the disease got spread to the entire world. As of February26, 2021, SARS-CoV-2 has infected 112.20 million people and caused 2.49 million deaths across the globe. Although the case fatality rate among SARS-CoV-2 patient is lower ( 2.15%) than its earlier relatives, SARS-CoV ( 9.5%) and MERS-CoV ( 34.4%), the SARS-CoV-2 has been observed to be more infectious and caused higher morbidity and mortality worldwide. As of now, only the knowledge regarding potential transmission routes and the rapidly-developed diagnostics has been guiding the world for managing the disease indicating an immediate need for a detailed understanding of the pathogen and the disease-biology. Over a very short period of time, researchers have generated a lot of information in unprecedented ways in the key areas, including viral entry into the host, dominant mutation, potential transmission routes, diagnostic targets & their detection assays, potential therapeutic targets & drug molecules for inhibiting viral entry and/or its replication in the host including cross-neutralizing antibodies and vaccine candidates that could help us to combat the ongoing COVID-19 pandemic (Figure-1). In the current review, we have summarized the available knowledge about the pathogen and the disease, COVID-19. We believe that this readily available knowledgebase would serve as a valuable resource to the scientific and clinical community and may help in faster development of the solution to combat the disease.